2022
DOI: 10.15252/embr.202153509
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid‐derived growth factor (MYDGF) protects bone mass through inhibiting osteoclastogenesis and promoting osteoblast differentiation

Abstract: Whether bone marrow regulates bone metabolism through endocrine and paracrine mechanism remains largely unknown. Here, we found that (i) myeloid cell-specific myeloid-derived growth factor (MYDGF) deficiency decreased bone mass and bone strength in young and aged mice; (ii) myeloid cell-specific MYDGF restoration prevented decreases in bone mass and bone strength in MYDGF knockout mice; moreover, myeloid cell-derived MYDGF improved the progress of bone defects healing, prevented ovariectomy (OVX)-induced bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…On the other side of the disorder of osteohomeostasis, the engagement of Stat3 in osteoblast bone formation is likewise crucial. First, Stat3 upregulates Runx2 transcriptional activity, induces alkaline phosphatase (ALP) activation and calcium nodule mineralization by binding to the osteogenesis-associated transcription factor Runx2 ( Xu et al, 2022 ). The subsequent ChIP experiments reveal that Stat3 directly binds to the promoter of the late osteogenic marker osteocalcin (OCN) and further enhances this effect upon the incorporation of Runx2 ( Xu et al, 2020 ).…”
Section: The Role Of Signal Transducer and Activator Of Transcription...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side of the disorder of osteohomeostasis, the engagement of Stat3 in osteoblast bone formation is likewise crucial. First, Stat3 upregulates Runx2 transcriptional activity, induces alkaline phosphatase (ALP) activation and calcium nodule mineralization by binding to the osteogenesis-associated transcription factor Runx2 ( Xu et al, 2022 ). The subsequent ChIP experiments reveal that Stat3 directly binds to the promoter of the late osteogenic marker osteocalcin (OCN) and further enhances this effect upon the incorporation of Runx2 ( Xu et al, 2020 ).…”
Section: The Role Of Signal Transducer and Activator Of Transcription...mentioning
confidence: 99%
“…Elevated leptin in serum induces activation of Stat3 in cartilage and leads to pathological activation of CD14/TLR4, which further provokes obesity-associated inflammation and MMP-13 expression ( Jiang et al, 2021 ). Analogously, the myeloid-derived growth factor (MYDGF) increases Stat3 phosphorylation on S727 ( Xu et al, 2022 ). MYDGF promotes bone defect healing by promoting ALP activity and mineralization in primary cranial osteoblasts, in which Stat3 activation plays a pivotal role ( Xu et al, 2022 ).…”
Section: Target Signal Transducer and Activator Of Transcription 3 Si...mentioning
confidence: 99%
See 1 more Smart Citation
“…For FM, the meta-analysis on HRT presented a positive effect in reducing FM, which is also consistent with our previous findings that ovariectomy-induced bone loss in mice tends to display a markedly increased body weight. [35] Of note, the meta-analysis still showed substantial heterogeneity ( I 2 = 67.0%, Q = 30.34). Therefore, we conducted the subgroup analyses on study region, age, duration of follow-up, and study type to find out the possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…A Liedert et al found that The growth factor midkine (Mdk) plays a key role in bone remodeling, and it is expressed in the processes of bone formation and fracture repair ( Liedert et al, 2014 ). A recent in vivo animal study reported that myelogenous growth factor (MYDGF) protects bone mass by inhibiting osteoclastogenesis and promoting osteoblast differentiation, and is a positive modulator of bone homeostasis ( Xu et al, 2022 ). Similarly, growth factors play an important role in the repair of joint injuries.…”
Section: Functionmentioning
confidence: 99%